2009
DOI: 10.3109/17453670903170505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of instrumentation in lumbar spinal fusion in elderly patients

Abstract: Background and purpose An increasing number of lumbar fusions are performed using allograft to avoid donor-site pain. In elderly patients, fusion potential is reduced and the patient may need supplementary stability to achieve a solid fusion if allograft is used. We investigated the effect of instrumentation in lumbar spinal fusion performed with fresh frozen allograft in elderly patients.Methods 94 patients, mean age 70 (60–88) years, who underwent posterolateral spinal fusion either non-instrumented (51 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Studies show that clinical outcomes such as pain and disability following spinal fusion improve for 12 months, with little further improvement or even worsening after this point. 38,39 Our results suggest MIS is just as effective as open spinal fusion, similar to other studies. 3,40 However, a study by Kasis 18 comparing PLIF procedures (standard compared to less-invasive) found significantly greater improvements for the less invasive PLIF group.…”
Section: Discussionsupporting
confidence: 90%
“…Studies show that clinical outcomes such as pain and disability following spinal fusion improve for 12 months, with little further improvement or even worsening after this point. 38,39 Our results suggest MIS is just as effective as open spinal fusion, similar to other studies. 3,40 However, a study by Kasis 18 comparing PLIF procedures (standard compared to less-invasive) found significantly greater improvements for the less invasive PLIF group.…”
Section: Discussionsupporting
confidence: 90%
“…Carreon et al reported an increased risk of perioperative complications in elderly patients who underwent spine fusion [30]. Instrumented spinal fusion in elderly patients is also associated with complications due to the risk of screw loosening from poor bone quality even though spinal instrumentation has been shown to increase fusion rates compared to non-instrumented fusion [31][32][33]. Okuyama et al published a study examining the influence of bone mineral density (BMD) on pedicle screw fixation augmenting posterior lumbar interbody fusion in elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…The next step then is to prove evidence of a consistent long-term effect of fusion surgery in the population of older patients. Several studies have done this and shown stable results, both at short term up to 2 years and at longterm follow-up [4,6,29]. So cost-effectiveness of fusion surgery in the older patients in a long-term perspective might be expected, but still needs to be documented.…”
Section: Discussionmentioning
confidence: 98%
“…All patients underwent uninstrumented lumbar spinal fusion using fresh frozen allograft with or without direct-current stimulation. The second cohort was an observational cohort of 94 patients who underwent either uninstrumented spinal fusion (51 patients) or fusion using pedicle screw instrumentation (43 patients) [4]. Reasons for surgery in this cohort were the same as in the other group and all fusions were performed using fresh-frozen allograft.…”
Section: Patient Populationmentioning
confidence: 99%